Obstetric and perinatal outcomes in women with multiple pregnancy in Altai region - S. V. Barinov; A. A. Belinina; I. V. Molchanova; O. V. Kolyado (Фундаментальная и клиническая медицина, 2019)
Aim. To study complications and perinatal outcomes of multiple pregnancy in women of the Altai Region.Materials and Methods. We recruited 678 consecutive pregnant women, including 378 with multiple pregnancy, with the subsequent analysis of clinical and ultrasound examination data as well as perinatal outcomes.Results. Women with multiple pregnancy were characterised by a significantly higher rate of gynecological and somatic diseases including pregnancy-related anemia (20.2% versus 4.3% in women with multiple and singleton pregnancy, respectively, OR = 6.0, 95% CI = 3.2-11.3). Further, multiple pregnancy was a significant risk factor for preterm birth (62.26% and 21.82%, respectively, OR = 5.9, 95% CI = 4.2-8.4, p ≤ 0.001). Application of cervical pessary was able to prolong the multiple pregnancy for 4 weeks.Conclusion. Prevention of threatening preterm birth in women with a multiple pregnancy using a cervical pessary improves perinatal outcomes.